2011
DOI: 10.48550/arxiv.1103.2225
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Absence of Relativistic Stars in f(T) Gravity

Abstract: In this work we investigate the structure of neutron stars in modified f (T ) gravity models. We find that, unlike the f (R) models, the equations of motion put a rather strict constraint on the possible f (T ) functions. Specifically, after analyzing the problem in two different choice of coordinates with spherical symmetry, we conclude that the relativistic neutron star solution in f (T ) gravity models is possible only if f (T ) is a linear function of the torsion scalar T , that is in the case of Teleparal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 18 publications
0
46
0
Order By: Relevance
“…f ,T T = 0 puts a strict restriction on the choice of f (T ) function to a linear one. As a result, only if f (T ) is a linear function of the torsion scalar T , one can leads to the existence of neutron star solution [92]. In a recent paper, [91,92] suggested that, instead of choosing f ,T T = 0, if one consider T ′ = 0 or T = T 0 , the solution yields a constant energy density and pressure, obeying the dark energy equation of state or the pressure which blows up at r → 0.…”
Section: Resultsmentioning
confidence: 99%
“…f ,T T = 0 puts a strict restriction on the choice of f (T ) function to a linear one. As a result, only if f (T ) is a linear function of the torsion scalar T , one can leads to the existence of neutron star solution [92]. In a recent paper, [91,92] suggested that, instead of choosing f ,T T = 0, if one consider T ′ = 0 or T = T 0 , the solution yields a constant energy density and pressure, obeying the dark energy equation of state or the pressure which blows up at r → 0.…”
Section: Resultsmentioning
confidence: 99%
“…The equations of motion of the non-diagonal case are quite different from the previous ones of the diagonal case. This is the proof of the dependence on the frame in f (T ) theory [26]. In such a situation, the physics that results from this set of equations must present new data that may be important in understanding the subjects that still require attention in Cosmology and Astrophysics.…”
Section: A Set Of Non-diagonal Tetradmentioning
confidence: 85%
“…An imposition of the form (26) has been obtained for a set of diagonal tetrads in the case of a spherically symmetric and static metric [19,20]. In the next section, we will see the case where it will be taken a set of non-diagonal tetrads for describing the metric of LTB (18).…”
Section: The Geometry Of An Inhomogeneous Universementioning
confidence: 99%
“…Deliduman and Yapiskan [24] have observed the constraint on the neutron solution in f (T ) theory of gravity and concluded that the solution is possible only for a linear function of torsion. Cai et al [25] have discussed the matter bounce cosmology with scalar and tensor modes of cosmological perturbations.…”
Section: Introductionmentioning
confidence: 99%